An Analysis of Taliban Conflict in daily Dawn during Three Regimes in Pakistan - Imran ul Haq; Shabir Hussain (Journal of Peace, Development and Communication, 2023)
This study analyzes news reports on the Taliban conflict published in the daily Dawn newspaper to identify the factors responsible for shifts in press narratives in an environment of diverse and conflicting voices over the period 2001-2015. The study shows different reporting patterns during the governments of the Pakistan Muslim League Quaid-i-Azam, PML (Q) led by President Pervez Musharraf, the Pakistan Peoples Party (PPP), and the Pakistan Muslim League Nawaz (PML-N). Using quantitative content analysis and using the conceptual framework of political contest theory, this study examines how the competing positions of political actors were mediated by the journalistic agency. The results show that the selected newspaper treated the official and dissenting sources differently during different regimes, meaning that press support for official or dissenting sources constantly changed according to the changing political environment. In addition, the results related to the press’s treatment of tones in headlines indicate that the positive, negative, and neutral trend toward government policies during the Taliban conflict in different regimes did not remain static and was constantly changing.